Unusual presentation of inferior thyroid artery aneurysm: Case report - Kocatürk, Hasan; Karaman, Adern; Bayram, Ednan; Çolak, Mehmet Cengiz (My University, 2011)
We present a case with an aneurysm of inferior thyroid artery after minor trauma. A 44-year-old man was admitted with a left neck side swelling occurring after taking bath. Duplex ultrasound showed a mass of 24 x 25 mm with intracavitary turbulent flow in the left anterolateral supraclavicular region, suggesting an aneurysm possibly supplied by the origin of the left vertebral artery. However, selective angiography demonstrated a left inferior thyroid artery aneurysm formation. The patient was scheduled for coil embolization. However, he refused firstly. After detailed description more pros than cons, he is still considering this option. The reason for the aneurysm formation was possibly atherosclerotic in origin because he had risk factors for atherosclerosis. This case is important in that occurring after minor trauma in the presence of vascular insulting factors. Copyright © 2011 by Türkiye Klinikleri.
Keywords: Aneurysm; Arteries; Injuries; Thyroid gland